If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = x + 2x + -7 Reorder the terms: -10 = -7 + x + 2x Combine like terms: x + 2x = 3x -10 = -7 + 3x Solving -10 = -7 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -10 + -3x = -7 + 3x + -3x Combine like terms: 3x + -3x = 0 -10 + -3x = -7 + 0 -10 + -3x = -7 Add '10' to each side of the equation. -10 + 10 + -3x = -7 + 10 Combine like terms: -10 + 10 = 0 0 + -3x = -7 + 10 -3x = -7 + 10 Combine like terms: -7 + 10 = 3 -3x = 3 Divide each side by '-3'. x = -1 Simplifying x = -1
| -2(19-8t)=18 | | X/5.1 | | 7x-7+3x=73 | | -5x+8+4x=6 | | x-2-2*ln(x)=0 | | s-10=20.81 | | 6k-10=14 | | 2y+15=23 | | 30m+350=25m+400 | | 6/34=t/108 | | X-4x=54 | | 18=10n | | 5y-3=47 | | 747+(-60x)=0 | | 6(x-8)+54=60 | | 42=49-v | | 2.02b+4.30=2.00b+6.30 | | 2(x)+4(y)=20 | | 5/9w=-1/4 | | 2(x)+4(y)=64 | | 6/24=t/108 | | 9(x+5)+8x=164 | | 747+(-60)=300 | | x(x+12)=(x-4)2 | | X+750=3200 | | x=26-57 | | 5(3x+2)=-3(2x-4)-4x | | 174=121-w | | 31=-4x-5x-5 | | 2e^4x+7=107 | | 182=42-y | | 9u+4u=30 |